A Randomized Clinical Trial of Oral Health-Related Quality of Life, Peri-Implant and Kinesiograph Parameters in Wearers of One-or Two-Implant Mandibular Overdentures - Policastro, Vivian Barnabé; Paleari, André Gustavo; Leite, Andressa Rosa Perin; Mendoza-Marin, Danny Omar; Cassiano, Ana Flávia Balestrero; Shaddox, Luciana Machion; Compagnoni, Marco Antonio; Pero, Ana Carolina (Wiley, 2018)
Purpose: The present randomized clinical trial compared the oral health-related quality of life (OHRQoL), peri-implant parameters, mandible movements, and maxillary complete denture movement during chewing between wearers of single- (1-IOD) and wearers of two-implant overdentures (2-IODs) for a period of 12 months. Materials and Methods: Twenty-one complete denture wearers were randomly allocated into two parallel groups: 1-IOD (n = 11) or 2-IODs (n = 10). The validated Brazilian version of the OHIP-EDENT was used to evaluate the OHRQoL. A kinesiograph recorded maxillary complete denture movement during chewing of hard food testing (polysulphide impression material) and soft food testing (bread). Peri-implant parameters were also recorded: plaque index (PI), bleeding on probing (BOP), and probing depth (PD). The Friedman test was used to compare the OHRQoL data and peri-implant parameters among periods; the Mann-Whitney test was performed to compare the groups (1- and 2-IODs). One-way ANOVA and the Bonferroni test were used to compare mandible movement during chewing among periods, and the t-test for independent samples was used to compare the groups. Maxillary complete denture movement was analyzed using three-way ANOVA followed by the Bonferroni test. All statistical analyses were performed at α = 0.05. Results: Both treatments led to better general OHRQoL in comparison to conventional complete dentures (p < 0.001). Better OHRQoL was observed among 2-IOD patients at the 12-month follow up (p = 0.034). Peri-implant parameters were similar irrespective of the group and follow-up period. Vertical opening was significantly higher among 1-IOD patients at 3 months (p = 0.038). Decreased maxillary denture vertical intrusions were observed with complete dentures in comparison with overdentures (p = 0.006), regardless of the food test (p = 0.251); however, vertical intrusion was significantly higher among 1-IOD patients (p = 0.043). Conclusions: This study suggested that 1-IOD can improve patient OHRQoL and may be similar to 2-IODs in preservation of both peri-implant parameters and masticatory movements.
Keywords: Complete denture; Implant; Kinesiograph; Mandibular overdenture; Mastication quality of life